The critical role of the industrial sector in reaching long-term emission reduction, energy efficiency and renewable targets. (15th January 2016) - Fais, Birgit; Sabio, Nagore; Strachan, Neil
Highlights: A new industrial modelling approach in a whole energy systems model is developed. The contribution of UK industry to long-term energy policy targets is analysed. Emission reductions of up to 77% can be achieved in the UK industry until 2050. The UK industry sector is essential for achieving the overall efficiency commitments. UK industry can make a moderate contribution to the expansion of renewable energies. Abstract: This paper evaluates the critical contribution of the industry sector to long-term decarbonisation, efficiency and renewable energy policy targets. Its methodological novelty is the incorporation of a process-oriented modelling approach based on a comprehensive technology database for the industry sector in a national energy system model for the UK (UKTM), allowing quantification of the role of both decarbonisation of upstream energy vectors and of mitigation options in the industrial sub-categories. This enhanced model is then applied in a comparative policy scenario analysis that explores various target dimensions on emission mitigation, renewable energy and energy efficiency at both a national and European level. The results show that ambitious emission cuts in the industry sector of up to 77% until 2050 compared to 2010 can be achieved. Moreover, with a reduction in industrial energy demand of up to 31% between 2010 and 2050, the sector is essential for achieving the overall efficiency commitments. The industry sector also makes a moderate contribution to the expansion of renewable energies mostly through the use of biomass for low-temperature heating services. However, additional sub-targets on renewable sources and energy efficiency need to be assessed critically, as they can significantly distort the cost-efficiency of the long-term mitigation pathway.